2017
DOI: 10.1371/journal.ppat.1006636
|View full text |Cite
|
Sign up to set email alerts
|

Nanobodies targeting norovirus capsid reveal functional epitopes and potential mechanisms of neutralization

Abstract: Norovirus is the leading cause of gastroenteritis worldwide. Despite recent developments in norovirus propagation in cell culture, these viruses are still challenging to grow routinely. Moreover, little is known on how norovirus infects the host cells, except that histo-blood group antigens (HBGAs) are important binding factors for infection and cell entry. Antibodies that bind at the HBGA pocket and block attachment to HBGAs are believed to neutralize the virus. However, additional neutralization epitopes els… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 74 publications
(64 reference statements)
3
68
1
Order By: Relevance
“…blocking epitope F with ´NERK´ motif (24), which may be less prone to sequence variations than HBGA binding sites and still block NoV binding to HBGA through allosteric interference. Moreover, two residues of ´NERK´ have been linked to GII.10 NoV blocking mechanism, suggesting possible involvement of this motif on NoV neutralization on larger scale (20). However, comparison of five putative GII.4 blockade antibody epitope sequences (12,25) (Table 4) did not provide more insights to superiority of GII.4-99 to induce GII.17 blocking antibodies, as GII.17 shared 12 aa residues with genetically more closely related GII.12 and only 6 aa with GII.4-99.…”
Section: Discussionmentioning
confidence: 99%
“…blocking epitope F with ´NERK´ motif (24), which may be less prone to sequence variations than HBGA binding sites and still block NoV binding to HBGA through allosteric interference. Moreover, two residues of ´NERK´ have been linked to GII.10 NoV blocking mechanism, suggesting possible involvement of this motif on NoV neutralization on larger scale (20). However, comparison of five putative GII.4 blockade antibody epitope sequences (12,25) (Table 4) did not provide more insights to superiority of GII.4-99 to induce GII.17 blocking antibodies, as GII.17 shared 12 aa residues with genetically more closely related GII.12 and only 6 aa with GII.4-99.…”
Section: Discussionmentioning
confidence: 99%
“…Serotype cross-neutralizing antibodies targeting the CD155-binding ‘canyon’ of the poliovirus capsid are rarely produced by the murine or human humoral immune systems, 79,80 but are apparently common in llama heavy-chain only responses. 81 Likewise, V H Hs targeting the HBGA-binding pocket of norovirus VP1 neutralized a broad range of genotypes, 82 while larger conventional antibodies also made contact with antigenically variable residues surrounding the HBGA pocket and were thus strain-specific. 83 …”
Section: Single-domain Antibodies Directed Against Folded Proteinsmentioning
confidence: 99%
“…Human noroviruses interact with histo-blood group antigens (HBGAs) (6)(7)(8)(16)(17)(18)(19)(20). Indeed, two recently developed human norovirus cell culture systems have shown that HBGAs and HBGA secretor status are important for virus infection (21,22).…”
mentioning
confidence: 99%